Effect of hydrosoluble polysaccharides of Macrocystis pyrifera on physiological and metabolic responses of Litopenaeus vannamei infected with Vibrio campbellii - Sánchez Campos, Liliana Noemi; Díaz, Fernando; Licea, Alexei; Re, Ana Denisse; Lizárraga, M. Leonardo; Flores, Maricela; González Sánchez, Ricardo; Tordoya Romero, Caroline (HIDROBIOLÓGICA, 2017)
Adult white shrimp Litopenaeus vannamei between 23 and 32 g of wet weight were injected or submerged in a hydrosoluble polysaccharides extract from Macrocystis pyrifera and infected with Vibrio campbellii. The infection decreased the oxygen consumption rate to 24 mg O2 h-1 kg-1 w.w., in shrimps of the control group, which were only infected with V. campbellii. Immunestimulated shrimps did not decrease their oxygen consumption rate at any hour p.i. (46 mg O2 h-1 kg-1 w.w.) maintaining it similar to the pre-injection group. Glucose level in the hemolymph of V. campbellii infected shrimps at two hours p.i. was significantly higher (p > 0.05) than the level of the pre-injection group. L. vannamei injected with the extract showed a significant decrease (p > 0.05) in their glucose level at 12 hours p.i., but at 24 hours p.i. it returned to normal level. Shrimps submerged in the extract showed no significant glucose level difference (p < 0.05). Lactate concentration in the hemolymph of the pre-injection group was 11.4 mg dL-1 , but adults injected with the extract had the lowest lactate levels throughout the experiment. Shrimps submerged in the extract decreased lactate levels at 6 and 12 hours p.i. but at 24 hours p.i. the level returned to 9.0 mg dL-1 . The total protein concentration in the hemolymph of pre-injection group was 115.3 mg mL-1 , shrimp injected with saline solution showed no significant differences (p < 0.05) compared to basal control; shrimps injected with V. campbellii had the lowest values of total proteins 6 hours p.i (p > 0.05) immunoestimulated shrimps showed an increase in their total proteins levels. This study concluded that administration of extract of M. pyrifera via injection and immersion in adult white shrimp can be used for immunostimulation purposes.